Analysis of the Consumption Patterns of Health Supplements in Health Care Worker in the Era of the COVID-19 Pandemic - Wening Sari (Nusantara Science and Technology Proceedings)
Health workers are at the forefront of handling COVID-19, so they have a high risk of contracting the virus. There have been 1.967 deaths in Indonesian health workers due to COVID-19, the highest number in Asia. While on the job, health workers must maintain a healthy immune system and use personal protective equipment. It is believed that taking vitamins, minerals, and herbs can help boost endurance. This study aims to examine the pattern of health supplement consumed in health workers during the COVID-19 pandemic. This research was conducted with a Cross-Sectional approach carried out on 100 health workers by providing questionnaires related to the types and effects of health supplements consumed by health workers in the era of the COVID-19 pandemic. From all respondents who took supplements, 75.2% consumed every day during the pandemic, whereas only 40.6% did before the pandemic. Prior to the pandemic, it was discovered that 33% of respondents took more than two types of health supplements. However, during the pandemic, it was revealed that 65% took more than two types of health supplements. There was an increase in respondents who took supplements believed to improve the immune system (80.2% vs 50.5%). Consumption of herbs and honey increased during the pandemic (19.8% vs 40.6%), with honey the most consumed. During the pandemic, health workers take more health supplements and a more comprehensive range of supplements.